The Existence of Pancasila for the Millenial Generation in Order to Realize the National Ideological Resistance in the Era of Disruption - Rahmawati, Elly (Jurnal Scientia Indonesia, 2016)
Building national character is an absolute and urgent need in the era of industrial revolution 4.0. In today’s era there has been a paradigm shift about how we get information, how we communicate, how we work and how we express things. This very rapid technological development has changed the way of life of today’s and future societies. The era of disruption as a result of the industrial revolution has resulted in may positive impacts such as damaging the nation’s mentality which is expected to destroy the joints of the life of the nation and the state. The rapid advancement of technology and social media facilitates the entry of various information and influences from outside including the value system and lifestyle which are often in conflict with the values of the Pancasila. If left unchecked the values of the Pancasila will be eroded by all kinds of global culture. Pancasila as a unifying idology as well as strnghening the integration of the Indonesian nation must now be attached more closely to the soul of the millennial generation. Todays youth nust be given an interesting and not boring touch of Pancasila learning with the use of technology and sosial media. This method is considered relevant to everyday life at this time so that the millennial generation can better understand the important of the Pancasila in reality.